Challenging Professions: Historical and Contemporary Perpectives on Women's Professional Work - Sugiman, Pamela (Relations industrielles / Industrial Relations, 2001)
Challenging Professions: Historical and Contemporary Perspectives on Women's Professional Work, edited by Elizabeth Smyth, Sandra Acker, Paula Bourne and Alison Prentice, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Careers; Female employees; History; Labor Unions; Occupational choice; Professionals; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z